Kontribusi Work Family Balance terhadap Work Engagement pada Karyawan Long Distance Marriage - Deby Amanda Putri; Tuti Rahmi (Pusat riset dan Inovasi Nasional, 2025)
This study aims to determine the contribution of work-family balance to work engagement in employees in long-distance marriages (LDM). The phenomenon of LDM is becoming increasingly common in the modern workplace, especially for couples who must live apart due to work demands in different locations. This condition can pose challenges in maintaining a balance between work and family life demands, which in turn can affect individual engagement in their work. Therefore, this study is important to understand the extent to which work-family balance plays a role in increasing the morale and work engagement of employees in LDM. This study involved 41 employees in LDM, with ages ranging from 24 to 50 years. The data collection method used two measuring instruments: the Utrecht Work Engagement Scale (UWES) developed by Schaufeli and Bakker (2004), and the work-family balance scale developed by Carlson et al. (2009). Data analysis was conducted using simple regression analysis techniques to determine the contribution of the independent variables to the dependent variable. The results showed that work-family balance contributed 65% to work engagement in employees in LDM. These findings indicate that the higher the level of work-family balance, the higher the employee's engagement in their work. Therefore, it is important for organizations to create policies and work environments that support work-family balance, especially for employees in long-distance marriages.